Are Fibromyalgia Patients Cognitively Impaired? Objective and Subjective Neuropsychological Evidence. Issue 1 (January 2015) - Tesio, Valentina; Torta, Diana M. E.; Colonna, Fabrizio; Leombruni, Paolo; Ghiggia, Ada; Fusaro, Enrico; Geminiani, Giuliano C.; Torta, Riccardo; Castelli, Lorys
<x xml:space="preserve">Abstract</x> Objective Patients with fibromyalgia (FM) syndrome often report a cluster of cognitive disorders that strongly interferes with their work and daily life, but the relationship between impaired cognitive function and self‐reported dysfunction remains unclear. We aimed to investigate the presence of cognitive impairments in patients with FM and to analyze the relationship between the impairments and their evaluation by the patients through a comparison with a group of healthy controls. Methods In total, 30 FM patients and 30 healthy controls performed a neuropsychological and clinical evaluation of short‐term, long‐term, and working memory; executive function; and self‐evaluation of cognitive impairment and depressive and anxiety symptoms. To thoroughly investigate executive function, we adopted the Miyake model that identifies 4 domains: shifting, inhibition, updating, and access. Results Our results confirmed the presence of impairments of attention, long‐term memory, working memory, and shifting and updating executive functions in FM patients compared with healthy controls. These impairments are reflected in patient reports independently of depressive symptoms. Conclusion The use of a self‐reported questionnaire in clinical practice would provide a first and easy screen for the presence of cognitive impairment in FM patients and, in most cases, obviate the need for a time‐consuming full neuropsychological test battery.